KURIKULUM BERBASIS KOMPETENSI DI SEKOLAH - Shodiq, Jafar (Andragogi: Jurnal Pendidikan Islam dan Manajemen Pendidikan Islam, 2024)
The Competency-Based Curriculum (CBC) aims to enhance the quality of education in Indonesia by emphasizing the development of relevant competencies for students. The main issue faced is the low quality of graduates due to the previous education system's focus on mastering content rather than specific skills. The objective of the CBC is to produce graduates who are proficient in knowledge, skills, and attitudes needed in the real world. The research used qualitative-descriptive methods, theoretical analysis, and literature studies. The results show that while the implementation of the CBC has been successful in certain aspects, it faces challenges such as increased teacher workload and inflexibility in adapting to local contexts. In conclusion, despite the challenges in implementation, the CBC provides an essential foundation for developing an education system that adapts to changing times, preparing globally competent graduates.